2016
DOI: 10.21776/ub.jkb.2016.029.03.4
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Penyebab Ketidaklengkapan Pengisian Rekam Medis Rawat Inap di Rumah Sakit Universitas Muhammadiyah Malang

Abstract: Program Studi Magister Manajemen Rumah Sakit Fakultas Kedokteran Universitas Brawijaya Malang 3Rumah Sakit Universitas Muhammadiyah Malang ABSTRAK Salah satu upaya untuk meningkatkan mutu sarana pelayanan kesehatan yaitu dengan meningkatkan mutu pelayanan rekam medis meliputi kelengkapan, kecepatan dan ketepatan dalam memberikan informasi untuk kebutuhan pelayanan kesehatan. Rekam medis yang lengkap dan akurat dapat digunakan sebagai referensi pelayanan kesehatan, dasar hukum (medico legal), menunjang informas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 0 publications
1
10
0
5
Order By: Relevance
“…with medical records officers. This is in line with research conducted by (Nurhaidah et al, 2016) which stated that the completeness of medical record files at the University of Muhammadiyah Malang Hospital was still very lacking, where out of 40 medical record files there was no complete filled file. This is due to the lack of doctor's attention to filling in medical record files completely, as well as the lack of time for doctors to fill in medical records.…”
Section: Resultssupporting
confidence: 89%
“…with medical records officers. This is in line with research conducted by (Nurhaidah et al, 2016) which stated that the completeness of medical record files at the University of Muhammadiyah Malang Hospital was still very lacking, where out of 40 medical record files there was no complete filled file. This is due to the lack of doctor's attention to filling in medical record files completely, as well as the lack of time for doctors to fill in medical records.…”
Section: Resultssupporting
confidence: 89%
“…More detailed studies have also been carried out, where this study not only looks for the percentage of incomplete medical record files but also searches for incompleteness that occurs on various sheets in the medical record file. Nurhaidah (2016) reported from 40 incomplete inpatient medical records files the highest percentage of incompleteness on the medical resume sheet. Winarti (2013) reported in her research at X hospital in Surabaya found the highest incompleteness on the history sheet of the disease, 18% of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Medical records are written documents which contain identity, anamneses, physical examination, medical support examinations, diagnoses, clinical pathway, and all services provided to patients and treatment both performed in inpatients, outpatients as well as emergency services. Recording and filing of medical records can be done by general practitioners, specialists, subspecialists, dentists, dental specialists, residents who are practicing, nurses and non-nurses paramedics [1][2] [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data tersebut digunakan untuk penyusunan berbagai perencanaan rumah sakit dan evaluasi pimpinan terhadap pelayanan kesehatan yang diberikan. Salah satu hal lain akibat ketidaklengkapan rekam medis adalah terhambatnya proses klaim asuransi oleh pihak ketiga yaitu BPJS Kesehatan karena di dalamnya terdapat penulisan diagnosa utama dan juga diagnosa tambahan lainnya yang berpengaruh terhadap besaran klaim asuransi yang diajukan (Nurhaidah, Harijanto and Djauhari, 2016). Selain itu juga ketidaklengkapan akan menghambat tertib administrasi yakni dokumen rekam medis yang seharusnya sudah berada di ruang rekam medis atau penyimpanan, masih dikembalikan lagi ke dokter penanggungjawab untuk dilengkapi (Lihawa, Mansur and Wahyuni, 2015).…”
Section: Jurnal Arsi/volume 6 Nomorunclassified